P418 Dose escalation of oral 5-aminosalicylic acid for ulcerative colitis with Mayo endoscopic subscore of one improves long-term prognosis: a one-year multicentre, open-label, randomized controlled trial. (30th January 2023) - Aoki, Y; Fukuda, T; Kiyohara, H; Yokoyama, A; Nakazawa, A; Yoshimatsu, Y; Sugimoto, S; Nanki, K; Mikami, Y; Fukuhara, K; Mizuno, S; Sujino, T; et al.
Abstract: Background: Endoscopic healing, one of the treatment targets for ulcerative colitis (UC), is commonly defined as Mayo endoscopic sub-score (MES) ≤1. Furthermore, patients in whom MES of 0 is achieved are at a lower risk of relapse than those with MES of 1. However, it is unclarified whether the therapeutic intervention of dose escalation of oral 5-aminosalicylic acid (5-ASA) improves the prognosis of UC patients in clinical remission with MES of 1. Methods: A multicentre, open-label, randomized, controlled trial was conducted among 5 hospitals in Japan from March 2018 to June 2022. Patients with UC, aged 16 years or older, treated with 5-ASA, in clinical remission and confirmed MES of 1 were enrolled. Patients receiving maintenance therapy other than oral 5-ASA and thiopurine (e.g., topical therapy, biologics) were excluded. Patients were randomly assigned to either the therapeutic intervention group (increased the dose of 5-ASA) or the control group (without any intervention). Concomitant use of immunomodulator (IM) was used for the stratification factor in the randomization. The primary endpoint was clinical relapse within one year. Relapse was defined as both (1) pMayo ≥3 or rectal bleeding sub-score ≥1, and (2) addition of any induction treatments for UC including topical agents. Predictive factors for relapse and adverse events (AEs) were investigated as the secondary outcomes. The predictive factors were explored in the multivariable Cox regression analysis. Results: Eighty-one patients were enrolled and randomly assigned into the therapeutic intervention or the control group, and two patients were excluded due to important protocol violations after the randomization. Finally, 79 patients (n=39; therapeutic intervention, n=40; control) were included in the full analysis set (FAS). In the FAS, 46 (58.2%) patients were male, and 20 (25.3%) patients were treated with IMs. The relapse within one year was less in the therapeutic intervention group (6/39; 15.4%) than the control group (15/40; 37.5%), significantly (P =0.026) (Fig.1). In the exploratory analysis for the predictors, concomitant use of IM was associated with relapse (hazard ratio, 2.52; 95% confidence interval, 1.04-6.12, P =0.041). There were three AEs in the therapeutic intervention group. Two patients complained of nausea, and the other complained of diarrhea and melena. All the AEs were improved after turning back the treatment to that before the intervention. Fig. 1. The proportion of patients relapsed within one year in the full analysis set (primary analysis). Conclusion: The dose escalation of oral 5-ASA reduced the relapse within one year in UC patients in clinical remission with MES of 1.